PERAN STAKEHOLDER DALAM PENGEMBANGAN DESA WISATA SINGAPADU TENGAH, KABUPATEN GIANYAR - Bila, Aura Salsa; Widana, Ida Bagus Gede Agung; Dianasari, Dewa Ayu Made Lily (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
The Singapadu Tengah Tourism Village has the potential to be developed and contribute economically to the community. The purpose of this study is to identify the roles and challenges of stakeholders in the development of the Central Singapadu Tourism Village. The research method used in this study is a qualitative descriptive approach involving in-depth interviews and direct field observations. The results of the study indicate that stakeholders from academia, business, the Village Government, and the Media have played their roles, but the results of these roles in tourism development in Central Singapadu Village have not been seen due to the lack of utilization and implementation of previous training and guidance. Meanwhile, the roles of the Pokdarwis community and the Gianyar Regency Tourism Office have not been maximized, as seen from the less than optimal roles they have played. This can be improved by increasing coordination and integrating their respective roles and functions. The challenge in developing Central Singapadu Tourism Village lies in the community's inability to fully focus due to having other primary jobs. The tourism village is considered more of an additional or alternative activity.